2016
DOI: 10.1097/j.pain.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Differences in regional homogeneity between patients with Crohn's disease with and without abdominal pain revealed by resting-state functional magnetic resonance imaging

Abstract: Abnormal pain processing in the central nervous system may be related to abdominal pain in patients with Crohn's disease (CD). The purpose of this study was to investigate changes in resting-state brain activity in CD patients in remission and its relationship with the presence of abdominal pain. Twenty-five CD patients with abdominal pain, 25 CD patients without abdominal pain, and 32 healthy subjects were scanned using a 3.0 T functional magnetic resonance imaging (fMRI) scanner. Regional homogeneity (ReHo) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 48 publications
(60 reference statements)
2
32
1
Order By: Relevance
“…Within the DMN, MPFC is decreased reciprocally with the left LP cortex. Altered pre-frontal cortex FC is consistent with previous studies of CD including differences in amplitude of low-frequency fluctuations (29), in regional homogeneity for CD patients without pain (28), and in relation to effective treatment (30). The altered FC between anterior (MPFC) and posterior (LP) nodes within the DMN is also consistent with previous work (29).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Within the DMN, MPFC is decreased reciprocally with the left LP cortex. Altered pre-frontal cortex FC is consistent with previous studies of CD including differences in amplitude of low-frequency fluctuations (29), in regional homogeneity for CD patients without pain (28), and in relation to effective treatment (30). The altered FC between anterior (MPFC) and posterior (LP) nodes within the DMN is also consistent with previous work (29).…”
Section: Discussionsupporting
confidence: 89%
“…Studies of brain structure in CD may be in agreement on one result, altered gray matter (GM) of the superior frontal gyrus, although laterality and direction of alteration are inconsistent (22)(23)(24). Studies of brain function in CD have reported numerous FC alterations with very little overlap (25)(26)(27)(28)(29)(30)(31)(32) aside from some agreement on changes in brain networks or regions involved in executive function and/or default mode (26,30,32). Our study aimed to identify brain structural and functional changes in CD as compared to HC.…”
Section: Introductionmentioning
confidence: 97%
“…Patients with symptoms of Crohn's disease routinely undergo MR enterography and/or MR of the pelvis and, in most cases, receive intravenous injections of GBCAs. In these patients fMRI has shown sensitivity to detect brain functional changes related to stress and pain …”
mentioning
confidence: 99%
“…In these patients fMRI has shown sensitivity to detect brain functional changes related to stress 27 and pain. 28 The purpose of this study was to test whether the gadolinium-associated hyperintensity on T 1 -weighted images of the DN of nonneurological adult patients is related to modifications of resting-state functional connectivity (RSFC) of the cerebellum and DN.…”
mentioning
confidence: 99%
“…signals may provide a clue that is likely associated with a noncompensatory reaction or unbalanced local functionality of the entire brain network. Bao et al 40 found that ReHo signals were reduced in the insula, middle cingulate cortex, and supplementary motor area in patients with abdominal pain. Using fMRI, Sawsan 41 also found that the signal of brain functional activity in the insula and medial prefrontal cortex was enhanced in patients with endometriosis-related pain, and the excitatory neurotransmitter in this area was significantly increased.…”
Section: Cg1mentioning
confidence: 99%